Acid Activation and Chemical Oxidation in the Synthesis of meso‐Tetraphenylporphyrin using a Mixed‐Solvent System. Issue 4 (29th March 2019) - Sun, Zhicheng; Jiao, Shouzheng; Li, Furong; Wen, Jinyue; Yu, Yanmin; Liu, Yuanyuan; Cao, Meijuan; Li, Luhai; Zhou, Yang; She, Yuanbin
Abstract: The specific roles of solvents in the synthesis of meso ‐tetraphenylporphyrin (TPP) using a classical mixed‐solvent of acetic acid, propionic acid, and nitrobenzene are unclear to date. In this work, we explored the acid‐activation process between benzaldehyde and pyrrole using DFT calculations. The catalytic role of carboxylic acids was proven by the formation of a carbocation intermediate. Moreover, the oxidation behavior of nitrobenzene or its analogs was studied by UV/Vis spectroscopy. In particular, the formation of the corresponding amides derived from the reduction of nitrobenzene and its analogs directly confirmed their oxidation behaviors. Specifically, yields of up to 38% of TPP can be obtained from nominally pure to quite pure using the mixed‐solvent method with meta ‐nitrotoluene as the oxidant. Abstract : Hand in hand : The acid activation of carboxylic acids and oxidation behavior of nitrobenzene or its analogs in tetraphenylporphyrin (TPP) synthesis using a mixed‐solvent method were confirmed by computational calculations and experimental characterizations, respectively.